Optimum buyer-vendor inventory model with coordination and price breaks. Issue 1 (March 2021) - Ismail, A.Mohamed; Muniappan, P.; Kirubhashankar, C.K.
Abstract: This study develop optimum inventory model for buyer-vendor with coordination and price breaks situation. We develop the production inventory model with screening for deteriorating product and disposed for damaged items. The coordination strategy the buyer takes decision for the damaged products. Integrated inventory total cost is developed for system optimum values are found by using Lagrange's multiplier technique. Various examples are given to illustrate the developed model.